Peatland fire regime across Riau peat hydrological unit, Indonesia - Rossita, Annuri; Boer, Rizaldi; Hein, Lars; Nurrochmat, Dodik; Riqqi, Akhmad (Forest and Society, 2023)
Peatland stretches across approximately 8% of Indonesia's land area. Peat fire disturbance, which affects the carbon dynamics of the ecosystem, will determine the country's vision for a long-term strategy for low carbon development. While the impact of excessive draining on peatland fire is well-known to the scientific community, much less is known about peatland fire regimes in distinctive land management systems. We examined the effect of land use, land management, and climatic factors in peatland fires. The examination was performed at the Peat Hydrological Unit at Gaung?Batang Tuaka, Riau, Indonesia. We used a semi-automatic approach to determine the area of burned peatland and used a spatial analysis tool to analyze the spatio-temporal pattern of peatland fire in the region. Our results demonstrate an increasing trend of peatland fires between 2001 and 2020, with 33% of the burned peatland undergoing multiple fires. The bulk of the burned land was covered by either wet shrubs or estate crops, with the area of burned wet shrub-land cover was two times higher than the burned estate crop-land cover. Concerning peatland draining, this study found a positive correlation between draining intensity, as represented by canal density, and burned area in peatland forests. In managed and unmanaged land, canal density had no apparent correlation with the area of peatland burned; however, we found that the weighted area of burned peatland was, on average, seven times higher in the unmanaged area compared to the managed area. These findings urgently demand an increase in community participation in the utilization of unmanaged land and prompt execution of peatland rewetting in drained peat forests. While the government of Indonesia has developed a social forestry and agrarian reform scheme to enable the legal utilization of unproductive land in forest areas, we argue that greater impacts can only be achieved if environmental services incentive schemes escalate non-party actors' participation.